Molecular Characterization of TEM-59 (IRT-17), a Novel Inhibitor-Resistant TEM-Derived β-Lactamase in a Clinical Isolate of Klebsiella oxytoca - Bermudes, H. (American Society for Microbiology, 1999)
A clinical isolate of Klebsiella oxytoca (Kox 443) was found to have a low-level resistance to broad-spectrum penicillins (MICs of amoxicillin and ticarcillin, 256 and 32 μg/ml, respectively), without substantial potentiation by 2 μg of clavulanic acid per ml (amoxicillin- and ticarcillin-clavulanate, 128 and 8 μg/ml, respectively), while being fully susceptible to cephalosporins and other β-lactam antibiotics. These resistances were carried by a ca. 50-kb conjugative plasmid that encodes a single β-lactamase with a pI of 5.6. Compared to TEM-2, this enzyme exhibited a 3- to 30-fold higher K(m) and a decreased maximal hydrolysis rate for β-lactams; higher concentrations of suicide inactivators (5- to 500-fold higher concentrations giving a 50% reduction in hydrolysis) were required for inhibition. Nucleotide sequence analysis revealed identity between the bla(TEM) gene of Kox 443 and the bla(TEM-2) gene, except for a single A-to-G change at position 590, leading to the amino acid change from Ser-130 Gly. This mutation has not been reported previously in the TEM type β-lactamases produced by clinical strains, and the novel enzyme was called TEM-59 (alternative name IRT-17). This is the first description of an inhibitor-resistant TEM-derived enzyme in the species K. oxytoca.